Doctors in Late Antiquity: Changes in Status of Medical Practitioners and the Effect of the Rise of Christianity - Wort, Thomas Cedric Boulet (Université d'Ottawa / University of Ottawa, 2025)
The field of medicine in Late Antiquity occupied a complex position between older Graeco-Roman traditions, and the expanding influence of Christianity. At this time, physicians continued to use the medical works of both Hippocrates and Galen, while also trying to adapt their practices to incorporate themselves in the newly Christian-predominant Western Roman Empire, the Roman East, and the later Successor Kingdoms. This thesis investigates how doctors were represented, what roles they played, how their status changed, how they adapted to survive during this time, and how Christianity played a major role in the reshaping of the medical world. While the legacy of classical medicine is well known and extensively studied, less attention has been given to the doctors themselves as professionals and people of influence at this time, which this thesis will aim to rectify. The main focus on the thesis is to provide an introduction to the topic of doctors in Late Antiquity through three chapters. The first contains a discussion of the types of sources which have been used and a brief history of doctors in Rome prior to Late Antiquity. The second elaborates on the new role doctors played at this time, being sent on diplomatic missions East to the Sassanians and why they were chosen, a brief section on education followed by some of the doctors about whom we know that have been compiled in the volumes of the PLRE and the trends that can be seen in each volume. The focus of the third chapter is on the influence of Christianity in Late Antique medicine, the foundation of the first hospitals, the rise of miracle culture, and how doctors fit into this restructured world of healing.
Keywords: Late Antiquity; Doctors; Medicine; Christianity; Hospitals